An Analysis of the Municipal Waste Management of Romania and Bulgaria in the European Context - Mari-Isabella Stan (Ovidius University Annals: Economic Sciences Series, 2022)
Since municipal waste accounts for 7% - 10% of all waste generated in the European Union, this issue drums up major interest at the institutional level, given that increasing the levels of collected waste poses significant challenges to the environment and human health. The European Union adopted a legislative package which promotes the shift towards a more sustainable development model, known as the circular economy. The aim of this article is to analyze the dynamics of municipal waste management in Romania and Bulgaria in the European context, as there are deficiencies in these countries’ implementation of the European waste management legislation. Eurostat’s data for the 2000-2020 time horizon was used for the undertaken analysis. The results of the study show that both Romania and Bulgaria are facing similar challenges in terms of waste management due to the fact that some of the European directives have not been transposed into the national legislation.